The SCO1731 methyltransferase modulates actinorhodin production and morphological differentiation of Streptomyces coelicolor A3(2) - Pisciotta, Annalisa (Sci Rep, 2018)
Streptomyces coelicolor is a Gram-positive microorganism often used as a model of physiological and morphological differentiation in streptomycetes, prolific producers of secondary metabolites with important biological activities. In the present study, we analysed Streptomyces coelicolor growth and differentiation in the presence of the hypo-methylating agent 5′-aza-2′-deoxycytidine (5-aza-dC) in order to investigate whether cytosine methylation has a role in differentiation. We found that cytosine demethylation caused a delay in spore germination, aerial mycelium development, sporulation, as well as a massive impairment of actinorhodin production. Thus, we searched for putative DNA methyltransferase genes in the genome and constructed a mutant of the SCO1731 gene. The analysis of the SCO1731::Tn5062 mutant strain demonstrated that inactivation of SCO1731 leads to a strong decrease of cytosine methylation and almost to the same phenotype obtained after 5-aza-dC treatment. Altogether, our data demonstrate that cytosine methylation influences morphological differentiation and actinorhodin production in S. coelicolor and expand our knowledge on this model bacterial system.